Adherence to UK dietary guidelines is associated with higher dietary intake of total and specific polyphenols compared with a traditional UK diet: further analysis of data from the Cardiovascular risk REduction Study: Supported by an Integrated Dietary Approach (CRESSIDA) randomised controlled trial. Issue 4 (17th December 2018) - Castro-Acosta, Monica L.; Sanders, Thomas A. B.; Reidlinger, Dianne P.; Darzi, Julia; Hall, Wendy L.
Abstract: Adherence to dietary guidelines (DG) may result in higher intake of polyphenols via increased consumption of fruits, vegetables and whole grains. We compared polyphenol dietary intake and urinary excretion between two intervention groups in the Cardiovascular risk REduction Study: Supported by an Integrated Dietary Approach study: a 12-week parallel-arm, randomised controlled trial ( n 161; sixty-four males, ninety-seven females; aged 40–70 years). One group adhered to UK DG, whereas the other group consumed a representative UK diet (control). We estimated polyphenol dietary intake, using a 4-d food diary (4-DFD) and FFQ, and analysed 24-h polyphenol urinary excretion by liquid chromatography-tandem MS on a subset of participants ( n 46 control; n 45 DG). A polyphenol food composition database for 4-DFD analysis was generated using Phenol-Explorer and USDA databases. Total polyphenol intake by 4-DFD at endpoint (geometric means with 95 % CI, adjusted for baseline and sex) was significantly higher in the DG group (1279 mg/d per 10 MJ; 1158, 1412) compared with the control group (1084 mg/d per 10 MJ; 980, 1197). The greater total polyphenol intake in the DG group was attributed to higher intake of anthocyanins, proanthocyanidins and hydroxycinnamic acids, with the primary food sources being fruits, cereal products, nuts and seeds. FFQ estimates of flavonoid intake also detected greater intake in DG compared with the control group. 24-h urinary excretion showed consistency with 4-DFD in their ability to discriminate between dietary intervention groups for six out of ten selected, individual polyphenols. In conclusion, following UK DG increased total polyphenol intake by approximately 20 %, but not all polyphenol subclasses corresponded with this finding.